An efficient certificateless aggregate signature scheme for vehicular ad-hoc networks - Malhi, Avleen Kaur; Batra, Shalini (Discrete Mathematics and Theoretical Computer Science, 2015)
Distributed Computing and Networking The state-of-the-art telecommunication technologies have widely been adapted for sensing the traffic related information and collection of it. Vehicular Ad-Hoc Networks (VANETs) have emerged as a novel technology for revolutionizing the driving experiences of human. The most effective and widely recognized way for mutual authentication among entities in VANETs is digital signature scheme. The new and attractive paradigm which eliminates the use of certificates in public key cryptography and solves the key escrow problem in identity based cryptography is certificateless cryptography. A new certificateless aggregate signature scheme is proposed in the paper for VANETs with constant pairing computations. Assuming the hardness of computational Diffie-Hellman Problem, the scheme is proved to be existentially unforgeable in the random oracle model against adaptive chosen-message attacks.